Geo-material provenance and technological properties investigation in Copper Age menhirs production at Allai (central-western Sardinia, Italy). Issue 2 (15th December 2017) - Serra, Marco; Mameli, Valentina; Cannas, Carla
ABSTRACT: During the 2 nd millennium BC anthropomorphic menhirs belonging to a 3 rd millennium BC sanctuary were reused as building material in the Arasseda Nuraghe (Sardinia, Italy). To analyse the Arasseda menhirs and the local Monte Ironi geological samples (presenting similar visual features), chemical (pXRF, ICP-OES, ICP-MS), mineralogical-chemical (PXRD) and physical (Mohs hardness) measurements were performed. Through the experimental data, the menhirs source provenance and the technological properties (workability, durability) of the raw material chosen for sculptural purposes during Copper Age were investigated. To the authors' knowledge this is the first archaeometric study on the Arasseda menhirs (the third on Sardinian menhirs) and one between the few recently developed on European megaliths.